Complexity of the floral pattern in ventilation panel of timber building in Kelantan and Terengganu - Shaffee, Nursuriani (2013)
Modern architecture is partly responsible for disappearance of wood carving in Malay architecture. Wood carving is an art that portrays the identity of Malay traditional architecture. There are more than 20 carved components of a traditional Malay building which include ventilation panels on walls and above doors and windows. However, little is known on the complexity of the carving which has been passed from a generation of woodcarver to another. This study aimed to identify the trend on the complexity pattern of floral motifs on the carved ventilation panels fitted on Malay traditional buildings which from the period of 1840s to 2000s in the states of Kelantan and Terengganu. Data of carving motif were obtained from a set of 16 measured drawings from the Centre for the Study of Built Environment in the Malay World (KALAM) at Universiti Teknologi Malaysia. From the drawings, 32 carved components were analyzed using point pattern and visual descriptive analysis to find the changes on floral motifs. The results were then triangulated with the views of two craftsmen. It was found that eight types of ventilation panels were used in four types of buildings which were palaces, mosques, houses and resorts. The patterns of the carving are categorized into floral design element, element design character, compositional pattern, principle design and principal form. For example, similarities and differences in floral design element existed in flowers, branches, tendrils, flower buds and leaves. As indicated by the value of variance to mean ratio, the complexity of carving differ from one building type to another. It means that the carvings found on mosques are not necessarily more complex than the palaces or houses. It also means that the pattern of buildings in Kelantan was not necessarily more complex than those in Terengganu or vice versa. The inconsistency on the complexity of pattern can be attributed to the reigning government, social status of owners, skills of craftsmen, and placements of carved components onto the buildings. Therefore, Malay woodcarving is an artwork which constantly evolving depending on particular function, environment and socio-cultural needs in the society.